Factors Related to the Midwives Work Performance on the Implementation of Obstetric Care Standard in Antenatal Care (Study in Primary Healthcare Centers with in Patient Unit in Gresik District) - Siti Hamidah; Laksmono Widagdo; Lucia Ratna Kartika (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2014)
AbstrakAKI di Kabupaten Gresik tahun 2011 sedikit menurun dibanding tahun 2010, dari 20 kematian ibu (105,91/100.000 KH) menjadi 19 kematian ibu (98,82/100.000 KH). AKB tahun 2010, 47 bayi (2,48/1000 KH)) menjadi 140 bayi (7,49/1000KH) tahun 2011. Hasil AMP; selain penyebab langsung, kematian juga karena penyebab tidak langsung yaitu keterlambatan deteksi dini komplikasi kehamilan. SAK ANC merupakan tugas yang harus dilaksanakan semua Bidan. Hasil monitoring IBI Kabupaten Gresik, 50% Bidan belum memberikan asuhan ANC sesuai standar. Tujuan penelitian untuk mengetahui faktor faktor yang berpengaruh terhadap Kinerja Bidan dalam Pelaksanaan SAK ANC di Puskesmas Rawat Inap Kabupaten Gresik.Metode penelitian; jenis penelitian kuantitatif dengan desain crossectional. Pengambilan data secara angket terstrukur dan observasi dokumentasi hasil kinerja ANC. Populasi semua Bidan Puskesmas Rawat Inap Kabupaten Gresik berjumlah 119 Bidan. Jumlah sampel 87 Bidan dipilih secara simple random sampling. Analisis bivariat dengan uji Chi square, multivariat dengan uji regresi logistik ganda. Hasil penelitian; Kinerja Bidan dalam Pelaksanaan SAKANC kurang (44,8%). Sistem Manajemen SAK kurang (55,2%). Kepemimpinan SAK kurang (55,2%). Kreativitas SAK kurang (57,5%). Pengetahuan SAK kurang (56,3%). Tidak ada hubungan antara Kepemimpinan, kreativitas dan pengetahuan dengan Kinerja Bidan dalam SAK ANC. Ada hubungan antara Sistem Manajemen SAK ANC dengan Kinerja Bidan dalam Pelaksanaan SAK ANC (p-Value 0,031<0,05). Ada pengaruh antara Sistem Manajemen SAKANC terhadap Kinerja Bidan dalam pelaksanaan SAK ANC, (p-Value 0,045<0,05).Disarankan pada Dinas Kesehatan, meninjau kembali PerMenKes N0 938/SK/MenKes/VIII/2007, menghimbau pelaksanaan SAK ANC pada Kepala Puskesmas, memfasilitasi pelatihan manajemen organisasi dan SAK ANC untuk Bidan, melakukan supervisi SAK ANC secara berkala. Kepala Puskesmas membuat SK pelaksanaan SAK ANC, membuat program pelatihan manajemen organisasi dan pelatihan SAK ANC, lebih intensif memonitoring kinerja Bidan. IBI melakukan monitoring, evaluasi, menindaklanjuti secara berkesinambungan. AbstractMaternal mortality rate (AKI) in Gresik district in 2011 slightly decreased compared to 2010, from 20 maternal deaths (105.91/100.000 live births) to 19 maternal deaths (98.82/100.000 live birth). The number of death infants in 2010 was 47 infants (2.48%), and it became 140 infants (7.49/1000 live birth) in 2011. Result of MP showed that besides direct cause of death, it was also resulted from indirect cause such as delay in conducting early detection of pregnancy complication. Obstetric standard of care (SAK) for ante natal care (ANC) was a task that should be implemented by all midwives. A monitoring done by IBI of Gresik district showed that 50% of midwives had not conducted ANC according to the standard. Objective of the study was to identify factors affecting work performance of midwives in the implementation of SAK ANC in the inpatient primary healthcare centers of Gresik district.This was a quantitative study with cross sectional approach. Data were collected using structured questionnaire and by conducting documentation observation toward results of ANC performance. Study population was all 119 midwives in the inpatient primary healthcare centers in Gresik district. Study samples were 87 midwives who were selected using simple random sampling method. Chi square test was applied in the bivariate analysis, and multiple logistic regressions were applied in the multivariate analysis.Results of the study showed that work performance of midwives in the implementation of SAK ANC was inadequate (44.8%), SAK management system was inadequate (55.2%), and knowledge on SAK was insufficient (56.3%). No association was found between work performance of midwives in the implementation of SAK ANC and leadership, creativity, knowledge. Significant association was found between SAK ANC management system and work performance of midwives in the implementation of SAK ANC (p: 0.031). There was an influence of SAK management system toward work performance of midwives in the implementation of SAK ANC (p: 0.045).District health office is suggested to review PerMenKes no. 938/SK/MenKes/VIII/2007, to advice heads of primary healthcare centers to implement the SAK ANC, to facilitate organization management training and SAK ANC training, to do more intensive monitoring of the work performance of midwives. Suggestions for IBI were to monitor, to evaluate, and to follow up the implementation of SAK ANC continuously.